Glucocorticoids employ the monomeric glucocorticoid receptor to potentiate vitamin D3 and parathyroid hormone‐induced osteoclastogenesis. Issue 12 (14th November 2019) - Conaway, H. Herschel; Henning, Petra; Lie, Antia; Tuckermann, Jan; Lerner, Ulf H.
Abstract : Glucocorticoid (GC) therapy decreases bone mass and increases the risk of fractures. We investigated interactions between the GC dexamethasone (DEX) and the bone resorptive agents 1, 25(OH)2 ‐vitamin D3 (D3) and parathyroid hormone (PTH) on osteoclastogenesis. We observed a synergistic potentiation of osteoclast progenitor cell differentiation and formation of osteoclasts when DEX was added to either D3‐ or PTH‐treated mouse bone marrow cell (BMC) cultures. Cotreatment of DEX with D3 or PTH increased gene encoding calcitonin receptor (Calcr), acid phosphatase 5, tartrate resistant (Acp5), cathepsin K (Ctsk), and TNF superfamily member 11 (Tnfsf11) mRNA, receptor activator of NF‐κB ligand protein (RANKL), numbers of osteoclasts on plastic, and pit formation and release of C‐terminal fragment of type I collagen from cells cultured on bone slices. Enhanced RANKL protein expression caused by D3 and DEX was absent in BMC from mice in which the GC receptor (GR) was deleted in stromal cells/osteoblasts. Synergistic interactions between DEX and D3 on RANKL and osteoclast formation were present in BMC from mice with attenuated GR dimerization. These data demonstrate that the GR cooperates with D3 and PTH signaling, causing massive osteoclastogenesis, which may explain the rapid bone loss observed with high dosages of GC treatment.—Conaway, H. H., Henning, P., Lie, A., Tuckermann, J., Lerner, U. H. Glucocorticoids employ the monomeric glucocorticoid receptor to potentiate vitamin D3 and parathyroid hormone‐induced osteoclastogenesis. FASEB J. 33, 14394‐14409 (2019). www.fasebj.org